Rescue intervention after three days of renal ischemia caused by acute complicated type B aortic dissection. (March 2018) - Lai, Chih-Hung; Chang, Keng-Hao; Chang, Szu-Ling; Lai, Hui-Chih; Lee, Wen-Lieng; Liu, Tsun-Jui
Complicated type B dissection is associated with a high mortality rate due to malperfusion syndrome or progression of the dissection for which aggressive therapy with an endovascular or surgical intervention is recommended. Herein, we present a patient who received a successful percutaneous rescue intervention after three days of renal ischemia caused by a complicated type B dissection. This type of rescue of percutaneous intervention with branch vessel stenting appears to be useful in treating malperfusion syndrome caused by aortic dissection, even after a period of organ ischemia.